WILLIAM WALLER HENING, 1 THE STATUTES AT LARGE; BEING A COLLECTION OF ALL THE LAWS OF VIRGINIA, FROM THE FIRST SESSION OF THE LEGISLATURE, IN THE YEAR 1619, at 173 (1823) (enacted 1632). - (:unkn) unknown (General Publisher, 1632)
Ordering that no man go or send abroad without being sufficiently well-armed.
--
Keywords: REQUIRED POSSESSION